Detection and quantification of liver fat with MRIT1 dixon sequence in patients with hepatic steatosis and it’s comparison with USG - Manoj Mathur; Gaurav Kumar Sethi; Jaswinder Kaur Mohi; Navkiran Kaur (International Journal of Medical Research and Review, 2018)
Introduction: Hepatic steatosis also known as fatty liver is due to abnormal and excessive accumulation of lipids with in hepatocytes. It is the most common chronic disease of liver. Magnetic resonance techniques can detect fatty liver more accurately than ultrasonography and become primary modalityto assess hepatic steatosis both quantitatively and qualitatively.Aims: The aims of this study were detection and quantification of liver fat by MR technique in patients of hepatic steatosis. Comparison of USG and MRI in detection and quantification of liver fat.Material and Methods: This cross-sectional study was carried out on 50 patients in Department of Radiodiagnosis, Government Medical College, Rajindra Hospital, Patiala in whom risk factors for hepatic steatosis were present. Considering T1 Dixon MRI of liver as reference its comparison with USG was done in these patients for detection of hepatic steatosis and quantification of liver fat.Results: USG had sensitivity 73.68%, specificity 66.67%, positive predictive value 87.50% and negative predictive value 44.44% as compared to MRI T1 Dixon sequence for detection of fatty liver. When grading of fatty liver on USG was compared with percentage quantification of liver fat on MRI T1 Dixon sequence of liver, there was considerable overlapping of fat percentage in each grade.Conclusion: Advantages of MRI as compared to USG is its more sensitivity and specificity for detection of hepatic steatosis, early detection of hepatc steatosis, quantify liver fat, objective and not observer dependent.